2004
DOI: 10.1007/s00213-004-1878-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the kappa opioid agonist U50,488 and the kappa opioid antagonist nor-binaltorphimine on choice between cocaine and food in rhesus monkeys

Abstract: These results suggest that continuous treatment with U50,488 produces a kappa receptor-mediated increase in the relative reinforcing effects of cocaine in comparison with food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…We have shown previously that norBNI alone does not alter cocaine vs. food choice (Hutsell et al, 2016; Negus, 2004), and the dose of norBNI used in the present study (10 mg/kg) has been shown previously to produce selective kappa antagonist effects for up to two weeks (Ko et al, 1998). Taken together, these results suggest that kappa receptor antagonism is not sufficient to enhance amphetamine-induced reductions in cocaine vs. food choice, and provide further support for the conclusion that effects of naltrexone were mediated by its antagonism of mu rather than kappa receptors.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…We have shown previously that norBNI alone does not alter cocaine vs. food choice (Hutsell et al, 2016; Negus, 2004), and the dose of norBNI used in the present study (10 mg/kg) has been shown previously to produce selective kappa antagonist effects for up to two weeks (Ko et al, 1998). Taken together, these results suggest that kappa receptor antagonism is not sufficient to enhance amphetamine-induced reductions in cocaine vs. food choice, and provide further support for the conclusion that effects of naltrexone were mediated by its antagonism of mu rather than kappa receptors.…”
Section: Discussionsupporting
confidence: 49%
“…Finally, the effects of 0.032 mg/kg/h amphetamine were also determined alone or in combination with the kappa antagonist norbinaltorphimine (norBNI) (10 mg/kg administered IM once on the first day of amphetamine treatment). The single-dose treatment regimen was based on previous studies to indicate that 10 mg/kg norBNI produces kappa antagonist effects for at least two weeks and does not alter cocaine vs. food choice when administered alone (Hutsell et al, 2016; Ko et al, 1998; Negus, 2004). Only one monkey received all treatments; other monkeys exhausted their catheterization sites, and these monkeys had to be replaced over the course of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has found that U50,488 decreases the number of total arm entries, which is thought to be an index of locomotor activity [33], in rats examined in the elevated plus maze [19, 34]. U50,488 has also been shown to decrease operant response rates [35]. In the current study, U50,488 injections led to an increase in responding on the previously ethanol-associated lever despite these motor-suppressive effects, suggesting that stimulation of KORs plays a significant role in the reinstatement of ethanol seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Two findings argue against this possibility. First, cocaine vs. food choice in this procedure is sensitive to many other manipulations that are thought to influence the relative reinforcing strength of cocaine, including magnitude of the drug and food reinforcers, fixed-ratio values for the drug and food choices, non-contingent food delivery, punishment of food or drug choice, treatment with monoamine releasers, and social rank (Negus, 2003; 2004; 2005a; 2005b; Czoty et al , 2005). Second, opioid withdrawal in opioid-dependent rhesus monkeys produces a robust increase in choice of opioid agonists over food (Spragg, 1940; Griffiths et al, 1975; Negus, 2006; Negus and Rice, 2009).…”
Section: Discussionmentioning
confidence: 99%